Perbandingan Teknik Penyimpanan Menggunakan Medium Yang Berbeda Terhadap Viabilitas Kapang Colletotrichum capsici dan Prycularia oryzae - R Rasyidah; Rini Fariani (Jurnal Pengelolaan Laboratorium Pendidikan, 2021)
Laboratory of Microbiology which is part of Basic Laboratory System in Faculty of Mathematics and Natural Sciences University of Lambung Mangkurat have commonly used as a place of various activities both science academic practice and research. This laboratory also provides analysis for samples and production. Microbial culture plays important rule in practical science of microorganism. Thus, continuous culture and preservation are highly required. Preservation and re-culture of microbes in the laboratory recently  using short-term preservation and periodic re-culture to a new medium, so it is necessary to conduct research on microbial preservation, especially molds with certain preservation techniques using different media. Colletotrichum capsici and Prycularia oryzae isolates were used in this study. The two molds were stored using different mediums: tapioca, 50% PDB + glycerol, and 50% PDB + liquid paraffin with a preservation period up to 1-3 months. The preserved mold was then cultured onto PDA medium to see its viability. The results of preservation of Colletotrichum capsici for 1-3 months using 3 different types of medium showed that 50% of liquid PDB-paraffin medium had the best viability compared to tapioca medium and 50% PDB-glycerol. Prycularia oryzae preserved for 1-3 months using tapioca medium, 50% PDB-glycerol, and 50% liquid PDB-paraffin cannot grow back.